2020
DOI: 10.1017/jfm.2020.643
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment of particles during the withdrawal of a fibre from a dilute suspension

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…In this simple model, the effect of particle size is reminiscent of what is observed for the entrainment of suspension in dip-coating experiments in various geometries 35,37 .…”
Section: Capture Of Particles In the Filmmentioning
confidence: 86%
“…In this simple model, the effect of particle size is reminiscent of what is observed for the entrainment of suspension in dip-coating experiments in various geometries 35,37 .…”
Section: Capture Of Particles In the Filmmentioning
confidence: 86%
“…The above condition is further modified as * > 0.24 0 0.75 by Sauret et al 66 reducing the threshold capillary number and hence the critical film thickness for entrainment. However, for cylindrical geometry like fiber and wires, Dincau et al 52 derived the expression considering the particle and cylinder radius as: * ≅ 0.645 [ 3 (1 + 2.53 1.85 1 + 1.79 0.85 )] 1.5…”
Section: Discussionmentioning
confidence: 99%
“…The minimum film thickness required for neutrally buoyant particle entrainment (ℎ * ) on plate geometry has been reported as ℎ * ≥ 2 65 . Recent experimental studies suggested ℎ * ≥ 0.33 for plate geometry 66 and ℎ * ≥ 1.1 for fiber geometry 52 . However, we found entrained particles even at lower ℎ * which further investigated in the next section.…”
Section: Influence Of Binder Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The configuration of isolated particles is simpler to describe because the particles do not interact with each other. This configuration was considered for flat plates (Colosqui, Morris & Stone 2013;Sauret et al 2019) and fibres (Dincau et al 2020). The two-dimensional numerical study of Colosqui et al (2013) has shown that an isolated particle can be entrained in the coating film if the particle diameter d is smaller than the thickness at the stagnation point h * .…”
Section: Introductionmentioning
confidence: 99%